Кримінологічна характеристика кримінальних правопорушень у сфері господарської діяльності - Омельян, Максим Валерійович (Державний податковий університет, 2024)
У рамках дисертаційного дослідження було здійснено теоретичне узагальнення та запропоноване нове вирішення наукової задачі щодо розроблення заходів запобігання кримінальних правопорушень у сфері господарської діяльності та способів удосконалення кримінального законодавства. Проаналізовано стан і рівень сучасної злочинності у сфері господарської діяльності в Україні, що в свою чергу наштовхує на проведення детальної характеристики злочинності в цій сфері.

Within the framework of the dissertation research, theoretical generalization was carried out and a new solution to the scientific problem was proposed regarding the development of measures to prevent criminal offenses in the field of economic activity and ways to improve criminal legislation. The scientific novelty of the author's results lies in the fact that the dissertation work, by its nature and content, is one of the first comprehensive monographic studies on the criminological characteristics of economic crime and prevention in this field. The study scientifically substantiates and proposes ways to improve prevention mechanisms, formulates and justifies a number of provisions and conclusions that are new in terms of conceptual development and important for criminological science and legal practice
Keywords: кримінальні правопорушення; сфера господарської діяльності; злочинність; запобігання; протидія; правоохоронні органи; злочинець; criminal offenses in the sphere of economic activity; economic activity; criminality in the sphere of economic activity; crime prevention; combating criminality; law enforcement agencies; criminological characteristics